2007
DOI: 10.1002/jcb.21259
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin and atorvastatin enhance gene expression of collagen type 1 and osteocalcin in primary human osteoblasts and MG‐63 cultures

Abstract: To clarify the mechanism of the stimulatory effect of statins on bone formation, we have assessed the effect of simvastatin and atorvastatin on osteoblast activity by analysing cell proliferation, as well as collagen, osteocalcin, and bone morphogenetic protein-2 (BMP2) gene expression in primary human osteoblast (hOB) and MG-63 cell line cultures. Explants of bone from patients without any metabolic disease under orthopedic hip procedures were used to obtain hOB. Cell cultures were established, synchronized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 34 publications
5
57
1
1
Order By: Relevance
“…Exogenous Cyr61 enhanced the growth of both types of osteoblastic cells, whereas simvastatin suppressed the proliferation. Our findings are in accordance with those of previous studies which showed that Cyr61 enhanced the proliferation of osteoblasts (33) and statins stimulated differentiation but induced growth arrest in osteoblasts (34). Since the responses were similar in the 2 cell types and U2OS cells have more stable biologic behavior and higher transfection efficiency, they were used to study the associated signaling pathway.…”
Section: Discussionsupporting
confidence: 92%
“…Exogenous Cyr61 enhanced the growth of both types of osteoblastic cells, whereas simvastatin suppressed the proliferation. Our findings are in accordance with those of previous studies which showed that Cyr61 enhanced the proliferation of osteoblasts (33) and statins stimulated differentiation but induced growth arrest in osteoblasts (34). Since the responses were similar in the 2 cell types and U2OS cells have more stable biologic behavior and higher transfection efficiency, they were used to study the associated signaling pathway.…”
Section: Discussionsupporting
confidence: 92%
“…RSV, similarly to our results after 24h incubation, showed absence of cytotoxicity in kidney cells in the concentration range of 0.001-100 µM [47]. In other studies in primary human osteoblasts and osteosarcoma cells, a cell viability above 85% was observed using simvastatin and atorvastatin with concentrations ranging from 0.001-1 µM [19]. In a human bladder carcinoma T24 cell line, lovastatin was found to be cytotoxic at a concentration of 50 µM [48].…”
Section: Discussionsupporting
confidence: 76%
“…The treatment with RSV had no effects on cell proliferation within the concentration range of 0.001-10 µM, and significantly reduced proliferation with 100 µM of RSV, which could be related to the higher cytotoxicity found with this dose. The antiproliferative effect of statins has been shown to be more evident in cultures of human bone marrow stromal cells [15] and primary human osteoblasts [19], while it was negligible with the MG-63 osteosarcoma cell line [19]. Therefore, the high growth rate of transformed osteoblastic cell lines could account for the lack of antiproliferative effects in these in vitro models.…”
Section: Discussionmentioning
confidence: 92%
“…Randomized controlled trials of the statin family are needed to confirm the risk of fractures (7). The statin family enhances the mRNA and protein expression levels of BMP-2 and vascular endothelial growth factor (VEGF) to stimulate osteoblastic functions and upregulate gene expression of extracellular matrices including osteocalcin, bone sialoprotein, collagens and proteoglycans (2,(8)(9)(10). Statins induce and accelerate bone formation locally, trigger early development of growth factors, regulate angiogenesis by VEGF, differentiate into osteoblasts or osteocytes, and cause bone mineralization (11)(12).…”
Section: Introductionmentioning
confidence: 99%